HEALTH RISK ASSESSMENT IN UTILITY AREA IN PT PERTAMINA LUBRICANT PRODUCTION UNIT GRESIK - Ardhini Nugrahaeni (Universitas Airlangga, 2020)
Health Risk Assessment (HRA) is one part of risk assessment. In the utility area at PT Pertamina Lubricant Production Unit of Gresik use a machines that have impact on health noise and temperature hazards. The aim of this study was to identify health risk assessment in the utility area at PT Pertamina Lubricant Production Unit Gresik. This was an observational descriptive study with cross sectional design. This study uses total population of 9 people consist of 1 supervisors Health Safety Enviroment (HSE), 3 HSE officer, and 5 workers. Primary data obtained from interviews, observations, noise and temperature measurements. Secondary data were got in the documents from the company. The collected data were assessed as likelihood and severity to count the risk. Afterward risk control assessed and residual risk is calculated. The results of this study showed that there were 3 steps of work with 6 potential hazard noise and temperature. The risk assessment has levels of risk medium risk and low risk. Medium risk was found in the boiler monitoring and compressor. Low risk was found in the stage of preparing CNG gas and turning on the machines. Control effectiveness is 75%. Residual risk has a low risk and no risk. It can be concluded that the potential hazard in the utility area was noise. Most of the risk found in this area was categorized as low risk. Risk control was properly implemented. If the recommendation of control properly implemented there will be no residual risk. The suggestions given are monitoring the implementation of controls, fit to work, use of PPE, socialization of the use of PPE, giving reward and punishment to motivate workers to safe behavior at workKeyword: health risk assessment, utility area, PT Pertamina Lubricant Production Unit Gresik